(untitled) - Tsurumi, Yoshi (New York, 1980)
This book provides a detailed treatment of the new Technology Transfer Regulation of Japan. The regulation has attracted strong opposition from industry and has wide ramifications, making the need for a book on the subject all the more compelling.
Keywords: Technology transfer,Manufacturing industries,Chuyển giao công nghệ,Ngành công nghiệp sản xuất; History,History,Lịch sử,Lịch sử; Japan,Japan,Nhật Bản,Nhật Bản